Chosen message attacks method against ECC implementations - Peng LUO; Hui-yun LI; Kun-peng WANG; Ya-wei WANG (Tongxin xuebao)
Chosen-message side-channel analysis attacks for public-key cryptosystems based on scalar multiplications was proposed, where special input point P is chosen to have the features of special y-coordinate to generate noticeable variations on power consumption or other side-channel information, between point doubling and addition operations, rendering distinguishable key bit information. Experimental results demonstrate that the proposed chosen message with simple side channel analysis method could effectively generate the noticeable variations. The method applies to the prime filed ECC cryptographic algorithms.